2022
DOI: 10.1001/jamanetworkopen.2021.44178
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Vamorolone in Duchenne Muscular Dystrophy

Abstract: This nonrandomized controlled trial examines efficacy of vamorolone treatment for Duchenne muscular dystrophy among boys compared with glucocorticoid treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 49 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…Despite continuous therapeutic developments [ 2–5 ], the current standard of care treatment for most DMD boys is glucocorticoid (GC) treatment [ 6 ]. In the UK, boys are prescribed prednisolone/prednisone or deflazacort, with a daily or intermittent (10 days on, 10 days off) regime [ 7 ]; however, other regimes are in use globally [ 8 ] and short-term data from clinical trials have shown that the GC derivative designed to reduce adverse events, Vamorolone, has similar efficacy [ 9 ]. The age at starting GC is also varied, with potential impacts on disease trajectory over time.…”
Section: Introductionmentioning
confidence: 99%
“…Despite continuous therapeutic developments [ 2–5 ], the current standard of care treatment for most DMD boys is glucocorticoid (GC) treatment [ 6 ]. In the UK, boys are prescribed prednisolone/prednisone or deflazacort, with a daily or intermittent (10 days on, 10 days off) regime [ 7 ]; however, other regimes are in use globally [ 8 ] and short-term data from clinical trials have shown that the GC derivative designed to reduce adverse events, Vamorolone, has similar efficacy [ 9 ]. The age at starting GC is also varied, with potential impacts on disease trajectory over time.…”
Section: Introductionmentioning
confidence: 99%
“…Vamorolone was well tolerated at doses up to 6.0 mg/kg/d, with only 5 of the 46 patients stopping the study early and for unrelated causes. Glucocorticoid-treated DNHS individuals experienced a significant growth delay compared to vamorolone-treated participants, whose height percentiles remained consistent throughout time (0.37 percentile/month; 95% CI, 0.23 to 0.52 percentile/month) [ 74 ]. Once vamorolone completes its clinical trials successfully, it will be available to serve DMD patients.…”
Section: Possible Therapeutic Approachesmentioning
confidence: 99%